Swedenborgite CaBa(Mn2Fe2)O7 with Spin Ordering on a Geometrically Frustrated, Polar, Non‐centrosymmetric S = 5/2 Lattice. Issue 21 (10th October 2017) - Valldor, Martin; Yadav, Ravi; Hozoi, Liviu; van den Brink, Jeroen; Maljuk, Andrey; Werner, Jochen; Scaravaggi, Francesco; Wolter, Anja U. B.; Büchner, Bernd
Abstract : By solid‐state reaction in closed ampoules, almost phase pure Swedenborgite CaBa(Mn2 Fe2 )O7 [ P 63 mc, a = 6.4100(1) Å, c = 10.3752(2) Å] was obtained. Thermodynamic and melting behavior investigations suggest that this complex oxide melts incongruently and that the true composition contains a minor surplus of Fe as compared to Mn. However, in first approximation, the magnetic transition metal lattice (Mn2 Fe2 ) can be described as a homogeneous S = 5/2 system and consists of kagome layers with an intermediate trigonal site. A long range antiferromagnetic ordering is observed at T N = 205.5 K, as proven by magnetometry and specific heat measurements. The S = 5/2 (high‐spin d 5 ) on‐site configuration is confirmed by ab initio quantum chemical calculations, which additionally indicate antiferromagnetic Heisenberg interactions with a ratio of 1.56 between the spin coupling constants of the two distinct d 5 –d 5 links (in and out of the kagome plane). In light of recent numerical studies for the extended Swedenborgite spin lattice, this quantum chemical estimate for the J out / J in ratio in combination with magneto‐electric coupling, as a consequence of the polar, non‐centrosymmetric crystal structure, explain the experimentally found antiferromagnetic order. Abstract :